A review of the causes, indicators, diagnosis and treatment of dental fluorosis - Farnaz Moshref-Javadi; Parastoo Afghari; Mojgan Rafizadeh; Mohammadreza Moharreri; Maryam Khoroushi (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Fluorosis is defined as a special form of injury to tooth structures, which is caused by excessive intake of fluoride during tooth development. The last fifty years have witnessed an increase in the incidence of fluorosis, necessitating special attention to the esthetic issues, diagnosis and treatment of these defects. The aim of this study was to investigate the causes, indicators, diagnosis and treatment of dental fluorosis.Review report: In this review article, the related articles were evaluated by running a Pubmed search from 1985 up to the present. After classification of the papers the most important relevant papers were selected and evaluated with an emphasis on practical therapeutic procedures.Results: Fluorosis appears when the fluoride content of drinking water is more than 1 ppm. Severity of fluorosis depends on the duration of exposure to fluoride. The host specific body response, weight, the extent of physical activity, nutritional factors, and bone growth and development result in different severities in individuals who have been exposed to the same fluoride level. Fluorosis is classified as very mild, mild, moderate and severe. There are three special indicators for dental fluorosis: Thylstrup and Fejerskov, Dean, and TSIF. Depending on the severity of fluorosis, different treatment modalities are recommended, including bleaching, microabrasion, macroabrasion, veneers and crowns. Conclusion: There are different classifications for fluorosis. In addition, there are specific indicators for fluorosis, each with some advantages and disadvantages. Treatment of fluorosis is different depending on the severity of the problem and treatment outcomes are usually satisfactory. Key words: Dental, Fluorosis, Therapy